Mortality Benefit of Convalescent Plasma in COVID-19: A Systematic Review and Meta-Analysis - Bansal, Vikas; Mahapure, Kiran S.; Mehra, Ishita; Bhurwal, Abhishek; Tekin, Aysun; Singh, Romil; Gupta, Ishita; Rathore, Sawai Singh; Khan, Hira; Deshpande, Sohiel; Gulati, Shivam; Armaly, Paige; et al. (Frontiers in Medicine, 2021)
Abstract Importance/Background: With a scarcity of high-grade evidence for COVID-19 treatment, researchers and health care providers across the world have resorted to classical and historical interventions. Immunotherapy with convalescent plasma (CPT) is one such therapeutic option. Methods: A systematized search was conducted for articles published between December 2019 and January 18th 2021focusing on convalescent plasma efficacy and safety in COVID-19. The primary outcomes were defined as mortality benefit in patients treated with convalescent plasma compared to standard therapy/placebo. The secondary outcome was pooled mortality rate and the adverse event rate in convalescent plasma-treated patients. Results: A total of 27,706 patients were included in the qualitative analysis and a total of 3262 (2127 in convalescent plasma-treated patients, 1135 in Non-convalescent plasma/control group) patients died. The quantitative synthesis in twenty-three studies showed that the odds of mortality on plasma therapy were significantly lower than patients who did not receive plasma therapy (OR 0.65, 95% CI 0.53-0.80, p<0.0001; I2=15%). Mortality benefit remains same even for fourteen trials/Prospective studies (OR 0.59, 95% CI 0.43-0.81, p=0.001 I2=22%) as well as for nine case series/retrospective observational studies (OR 0.78, 95% CI 0.65-0.94, p=0.01; I2=0%). However, in subgroup analysis for ten randomized controlled trials (RCTs), there was no statistically significant reduction in mortality between CPT compare to non-CPT (OR 0.76, 95% CI 0.53-1.08, p=0.13: I2=7%). Further sensitivity analysis of ten RCTs by excluding study with the highest statistical weight displayed a lower mortality rate compared to non-CPT COVID-19 patients (OR 0.64, 95% CI 0.42-0.97, p=0.04: I2=0%). The observed pooled mortality rate was 12.9% (95% CI 9.7-16.9%) and the pooled adverse event rate was 6.1% (95% CI 3.2-11.6) with significant heterogeneity. Conclusions and Relevance: Our systemic review and meta-analysis suggest, CPT could be an effective therapeutic option with promising evidence on the safety and reduced mortality in concomitant treatment for COVID-19 along with antiviral/antimicrobial drugs, steroids, and other supportive care. Future exploratory studies could benefit from more standardized reporting, especially of the timing of intervention and clinically relevant outcomes, like days until discharge from the hospital and improvement of clinical symptoms.